1998
DOI: 10.1164/ajrccm.158.2.9710012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Risk of Emphysema in Patients with Farmer's Lung and Matched Control Farmers

Abstract: We evaluated the long-term outcome of farmer's lung (FL) patients and matched control farmers using high-resolution computed tomography (HRCT). The study population consisted of 88 FL patients and 83 control farmers, matched by age, sex, and smoking habits. The mean time after the first diagnosed episode of FL was 14 yr. The great majority, 82%, of the studied subjects were nonsmokers. Clinical studies included HRCT, spirometry, and pulmonary diffusing capacity. Emphysema was found significantly more often (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
3
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 12 publications
5
34
3
3
Order By: Relevance
“…The results of this study confirm previous reports that emphysema is a more prevalent long term outcome of farmer's lung than interstitial lung fibrosis [14,16]. This is different than what has been reported in pigeon breeder's disease, where lung fibrosis is the major outcome [17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study confirm previous reports that emphysema is a more prevalent long term outcome of farmer's lung than interstitial lung fibrosis [14,16]. This is different than what has been reported in pigeon breeder's disease, where lung fibrosis is the major outcome [17].…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have usually reported only a small number of cases or, more importantly, have not thoroughly addressed the findings in patients with a past history of this disease. The present authors and others have previously shown that emphysema is an important sequela of farmer's lung [14,16]. In pigeon breeder's disease, interstitial fibrosis was the most important outcome in one study [17] while in another report 44% of chronic cases had emphysema [15].…”
mentioning
confidence: 45%
“…Nonetheless, for this patient, exposure to tobacco smoke could also explain the ventilatory dysfunction. Progression of HP to bronchial obstruction or emphysema is well recognized (10,32).…”
Section: Discussionmentioning
confidence: 99%
“…9,21 Emphysema is overrepresented in both smoking and non-smoking patients with chronic disease. 9,22 Associated honeycomb change is seen in about half of patients, and may be more common in those with pigeon breeder's lung. In patients with honeycomb change, the findings may be indistinguishable from UIP.…”
Section: Clinical Featuresmentioning
confidence: 99%